Pengaruh Tingkat Literasi Keuangan Syariah dan Kepercayaan terhadap Minat Menabung di Lembaga Keuangan Syariah - Maulidya Berliana Rahmawati; Miswan Ansori; Cahyaning Budi Utami (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research aims to find out whether there is an influence of sharia financial literacy and trust on people's interest in saving in sharia financial institutions. The research method used in this research is quantitative with data collection techniques through questionnaires. The object of this research is the people of Tengguli village, the majority of whom are Muslim. The research results show based on multiple linear regression analysis that sharia financial literacy and trust together have a significant influence on the interest in saving of the people of Tengguli village in sharia financial institutions. It is hoped that this research can be a reference for predicting interest in saving based on sharia financial literacy and trust, as well as consideration for financial practitioners in designing effective interventions to increase interest in saving through increasing sharia financial literacy and public trust. It is also hoped that further research can carry out research with a wider range of objects and with more diverse variables.